Pengaruh Kinetin Pada Pertumbuhan Kecambah Brokoli Hibrida (Brassica oleracea Var. Green Magic) Dan Kandungan Sulforafan Pada Kultur In Vitro - Monica Pamela Doodoh; Wenny Tilaar; Sesilia Wanget (Sam Ratulangi University, 2022)
This study aims to observe the growth in the sprouting phase and to observe the sulforaphane content in the growth stages of broccoli sprouts treated with kinetin on MS media. The research was conducted at the Laboratory of Biotechnology, Faculty of Agriculture, Sam Ratulangi University and the Laboratory of Department of Chemical Engineering, State of Malang. The study used a Completely Randomized Design (CRD) with 4 treatments and 9 replications, nam ely without kinetin, 0.5 ppm kinetin, 1 ppm kinetin, 1.5 ppm kinetin. The variables observed were the time of sprout formation, sprout height, sprout weight, sulforaphane content. The results of this study showed that the sulforaphane content was not affected by the height and weight of the sprouts but the kinetin concentration, the higher the concentration given, the higher the sulforaphane content.